COVID-19: What happened to the healthcare workers of a research and teaching hospital in Milan, Italy? COVID-19 Health Care Workers Hospital - Consonni, Dario; Bordini, Lorenzo; Nava, Carlo; Todaro, Aldo; Lunghi, Giovanna; Lombardi, Andrea; Magioni, Davide; De Palo, Francesco; Guerrieri, Lidia; Gatti, Michele; Serra, Daniele; Polonioli, Marco; et al. (Acta Biomedica Atenei Parmensis, 2020)
The paper wants to present the data of infection of the Health Care Workers of a research and teaching hospital in Milan, Italy. The majority (2554, 55.9%) of 4572 HCWs were tested for SARS-CoV-2 and 8.8% were found positive. Most of the tested workers were women, but we found higher relative frequency of positivity for men, even after adjustment for age, working area, and occupation. The higher frequency of positive tests in the medicine area is probably explained by the higher concentration in that area of COVID-19 patients. Conversely, the low frequency of positive HCWs in intensive care units is  probably explained by the diffuse and continuous use of PPD. Our results show that HCWs in a research and teaching hospital in the most hit Region in Italy had a similar pattern of infection as all other HCWs all over the world. The problem of SARS-CoV-2 infections among the hospital personnel HCWs should remind us  the concerns about hospital acquired infections both for patients and HCWs